Protein c-fos induction in rat brain and spinal dorsal horn by sincalide and opioids in vitro - Chen Su-zhen; Han Ji-sheng (Acta Pharmacologica Sinica, 2016)
Sincalide (CCK-8) is an antiopioid substance. In this study, we investigated the effects of sincalide and opioids on c-fos expression and their interaction in brain and spinal dorsal horn in vitro. Immunoprecipitation was used for detection of c-fos protein. The results indicated that 0.1 mumol.L-1 sincalide induced c-fos expression markedly in both brain (a 3.8-fold increase in c-fos protein level) and in spinal dorsal horn (a 3.6-fold increase). NDAP (a kappa receptor agonist) 0.1 mumol.L-1 showed some activating effects on c-fos expression, the c-fos protein level increased 2.7 and 2.6 times respectively in brain and spinal dorsal horn. Ohmefentanyl (Ohm, a mu receptor agonist) 0.1 mumol.L-1 also exhibited an inducing effect on c-fos protein production. Sincalide and NDAP exerted some additive effects on c-fos protein production in spinal cord. In contrast, the effect of sincalide on c-fos protein production is antagonistic to that of Ohm. The results suggested that there were changing patterns of interaction on c-fos expression between sincalide and opioids.